Efforts to Improve Students' Skills of MA Al Karim Central Bengkulu with Ethnoscience Learning Concept of Physics - Iwan Setiawan; Rosane Medriati; Andik Purwanto; Tiara Hardyanti Utama; Netriani Veminsyah Ahda; Muhammad Ataurrahman Aqil; Albet Karuniawan; Sm Farooque (Asosiasi Profesi Multimedia Indonesia, 2024)
This community service project aims to optimize the learning process by implementing ethnoscience-based physics instruction at MA Al Karim Bengkulu Tengah. The goal is to address the limitations of facilities and infrastructure that hinder the learning process, ultimately enhancing students' skills, knowledge, and academic performance. The program is carried out in several stages. The first stage involves an initial observation at MA Al Karim Bengkulu Tengah to obtain a detailed understanding of the school's conditions. The second stage includes outreach and coordination with the principal, teachers, and especially the physics teachers. The third stage involves providing skill training for the teachers on the concept of ethnoscience, which is then applied directly to the students during the learning process. The final stage consists of regular evaluations and mentoring involving MBKM students and physics teachers to ensure that the community service activities bring about improvements in the learning process. Through the ethnoscience training at MA Al Karim Bengkulu Tengah, it is hoped that both teachers and students will be able to enhance their skills and optimize the learning process despite the existing limitations in facilities and infrastructure. Based on the outcomes of this program, it can be concluded that the training had a positive impact on teachers' skills by utilizing the ethnoscience concept, which leverages the cultural diversity and local traditions of the community, even in the face of limited facilities and infrastructure. Ethnoscience concept can be very useful on improving learning activity at the school and also will enhance the learning experience.